PERSEPSI TUGAS MEDIATOR DALAM MENYELESAIKAN PERKARA PERCERAIAN DI KOTA MALANG INDONESIA - Sadili, M. Hasan; Jazari, Ibnu; Subekti, Ahmad; Albaritsi, Harun (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
In carrying out married life, husband and wife have their respective roles and functions in maintaining family harmony and harmony. If someone's role does not go well, it can cause disruption or problems within the family. Efforts to reconcile the two parties to a dispute in the realm of judicial law are called mediation. The research aims to reveal the perspective of the mediator's duties according to the views of mediation officers at the Malang City Religious Court office. The application of research using qualitative methods is research that is able to produce analytical procedures without static analysis procedures or by using other quantification methods. The mediation mechanism at the Malang City Religious Court is in accordance with PERMA Regulation Number 1 of 2008, namely: Regarding the mediation process, after the parties choose a mediator to mediate their case, the parties provide a resume of their case to the mediator. If they fail to choose a mediator, then the case files are handed over to the mediator who has been chosen by the Chair of the Assembly. The influence of the mediator in making the case a success can affect the Judicial Body and also the public's trust in the Judicial Institution. The mediator's success in resolving cases can ease the burden on the Chairman of the Panel in handling burdensome divorce cases. The mediator's efforts in completing mediation can be said to be composed of the role, function, duties and authority of the mediator. It can be said that all the mediator's efforts, whether through his authority, the mediator cannot force a complete reconciliation or not to divorce. However, on the contrary, through the function, role, authority and skills of the mediator, peace can be created between the parties.   Keywords : Mediator, Mediation, Divorce, Peace